2013
DOI: 10.1002/grl.50566
|View full text |Cite
|
Sign up to set email alerts
|

Separation and location of microseism sources

Abstract: [1] Microseisms are ground vibrations caused largely by ocean gravity waves. Multiple spatially separate noise sources may be coincidentally active. A method for source separation and individual wavefield retrieval of microseisms using a single pair of seismic stations is introduced, and a method of back azimuth estimation assuming Rayleighwave arrivals of microseisms is described. These methods are combined to separate and locate sources of microseisms in a synthetic model and then applied to field microseism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Through the following years, several research papers were published that demonstrated agreement with these conclusions (e.g., Schimmel et al, 2011;Moni et al, 2013;Sergeant et al, 2013). Besides the seasonal variability, seismic noise is also dependent on the station location within continents, close to the coast, or on islands (e.g., Stutzmann et al, 2009).…”
Section: Introductionmentioning
confidence: 76%
“…Through the following years, several research papers were published that demonstrated agreement with these conclusions (e.g., Schimmel et al, 2011;Moni et al, 2013;Sergeant et al, 2013). Besides the seasonal variability, seismic noise is also dependent on the station location within continents, close to the coast, or on islands (e.g., Stutzmann et al, 2009).…”
Section: Introductionmentioning
confidence: 76%
“…While the resolution and pattern recognition capabilities of the human auditory system are generally well known [e.g., Hartmann, 1999;Wang and Brown, 2006a], the seismology community does not entirely appreciate the potential of auditory display as a tool for seismic data analysis. A case in point is the interesting work of Moni et al [2012] and Moni et al [2013],…”
Section: Discussionmentioning
confidence: 99%
“…BSS can be used to separate signals with different slowness from these mixtures. Based on this idea, a BSS method called DUET has been used in different settings to unmix signals from the volcano Mt Etna (Moni et al 2012), and also from secondary microseisms (Moni et al 2013).…”
Section: Introductionmentioning
confidence: 99%